Sympathetic innervation controls homeostasis of neuromuscular junctions in health and disease - Khan, Muzamil Majid; Wild, Franziska; Labeit, Dittmar; Labeit, Siegfried; Rudolf, Rüdiger (Proceedings of the National Academy of Sciences of the United States of America, 2016)
The distribution and function of sympathetic innervation in skeletal muscle have largely remained elusive. Here we demonstrate that sympathetic neurons make close contact with neuromuscular junctions and form a network in skeletal muscle that may functionally couple different targets including blood vessels, motor neurons, and muscle fibers. Direct stimulation of sympathetic neurons led to activation of muscle postsynaptic β2-adrenoreceptor (ADRB2), cAMP production, and import of the transcriptional coactivator peroxisome proliferator-activated receptor γ-coactivator 1α (PPARGC1A) into myonuclei. Electrophysiological and morphological deficits of neuromuscular junctions upon sympathectomy and in myasthenic mice were rescued by sympathicomimetic treatment. In conclusion, this study identifies the neuromuscular junction as a target of the sympathetic nervous system and shows that sympathetic input is crucial for synapse maintenance and function.